Using Chemistry Teaching Aids Based Local Wisdom as an Alternative Media for Chemistry Teaching and Learning - Erfan Priyambodo; Safira Wulaningrum (International Journal of Evaluation and Research in Education (IJERE), 2017)
Students have difficulties in relating the chemistry phenomena they learned and the life around them. It is necessary to have teaching aids which can help them to relate between chemistry with the phenomena occurred in everyday life, which is chemistry’s teaching aids based on local wisdom. There are 3 teaching aids which used in chemistry teaching and learning, i.e. clay molymod, electrolyte tester, electroplating tool. The chemistry teaching aids was reviewed by media experts, material experts, and also reviewers. The reviewers’ assessment showed that all of the teaching aids have a very good quality. Based on the response from Senior High School’ students, they all agree that the teaching learning process using the teaching aids could improve their learning motivations.